Evaluation of antifungal activity and cytotoxicity of Thymus vulgaris essential oil - Al-Shahrani, Mohammed Hamed; Mahfoud, Maysa; Anvarbatcha, Riyasdeen; Athar, Md Tanwir; Asmari, Abdulrahman Al (Pharmacognosy Communications)
Objective: To evaluate the antimicrobial properties of Thymus vulgaris against seven pathogenic fungi strains and its cytotoxic effect on a human breast cancer cell line (MDA-MB-231) Methods: The susceptibility test was carried out in terms of by determining minimal inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) using micro-dilution methods and additional end point by using MTS chromogenic assay. Cytoto- xicity activity was assessed using MTT assay, the viability and the IC50 were used to evaluate this test. Results: All tested fungal strains were sensitive to the (Thymus vulgaris essential oil) TEO and this inhibitory effect is dose-dependent. A remarkable (p<0.001) inhibitory effect at concentra- tions 2.5-10mg/ml for all tested organisms comparable with control was found. The MIC50 values ranged between 0.5 to 5mg/ml. The MFC values varied from 2.5–10 mg/mL and were equal to MIC values for majority of the tested organisms. As far as the antifungal activity is concern, out of the seven strains tested, Candida kefyr exhibited the highest sensitivity with minimal inhibition growth 2.5mg/ml whereas, Aspergillus niger exhibited the lowest inhibition ≥10mg/ml. Thymus vulgaris oil inhibited proliferation of MDA-MD-231 cancer cells in a time- and dose dependent manner. IC50 value of the complex was found to be time dependent. At 24h treatment, the IC50 values ranging between 108-115μg/ml, while at 48h treatment the values were between 71-78μg/ml against cancer cell. Conclusion: Thymus vulgaris essential oil exhibited significant antifungal and cytotoxic effects on living cells. Therefore, it can be used as alternative antifungal natural substances and also play a significant role in discovery of the new drugs.
Keywords: Antifungal; cytotoxicity; Thymus; MTT assay; MIC